Keperawatan Spiritual di Bali - Kadek Yudi Aryawan; Ni Kadek Diah Purnamayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the description of spiritual nursing in Bali. The research method used is quantitative observational research with a cross-sectional approach. The research results on the fulfillment of spiritual needs by nurses in Bali are primarily in the medium category of 50%. At the same time, 32.5% are in the high class. Only 17.5% are in a common type. The fulfillment of spiritual needs by nurses in Bali is mainly in the medium and high categories. Only a tiny proportion of spiritual realization is in a low type. Caring has been embedded in nursing care, which is a form of implementing the spiritual dimension. In conclusion, the nurse's activity in implementing the concept of caring is an indirect part of spiritual care. A holistic and humanist approach is a strategy that needs to be instilled as part of professional nursing care. The aspect of spirituality is an essential dimension for providing excellent care in the era of disruption. Keywords: Tourism Health, Spiritual Nursing